Intracellular delivery of radioimmunoconjugates that target the cancer testis antigen, NY-ESO-1 - Chu, H (2013)
Cancer testis antigens (CTA) represent attractive targets for targeted radiotherapy and imaging as their expression is restricted to cancer and germ cells. NY-ESO-1, a member of the CTA family, is highly immunogenic and expressed in multiple tumor types including carcinoma of bladder, liver lung. The aim of this study was to develop radioimmunoconjugates (RIC) to target NY-ESO-1 protein in cancer cells. Anti-NY-ESO-1 antibodies were modified by addition of DTPA for 111In-labelling or, in the presence of Iodogen, were 123I-labelled. Delivery of radiolabeled immunoconjugates across the cell membrane was achieved using a protein transfection (PT) reagent (SAINT-PhD) and by chemical linkage with the cell-penetrating and nuclear-localizing peptide, TAT (YGRKKRRQRRR). Cellular internalization, distribution and efflux of 111In-DTPA-anti-NY-ESO-1-TAT-PT and 123I-anti-NY-ESO-1-TAT-PT were investigated in cell fractionation and retention assays. It was shown that protein transfection reagent has promoted the cellular uptake of RICs into SK-MEL-37 and both of 111In-DTPA-anti-NY-ESO-1-TAT-PT and 123I-anti-NY-ESO-1-TAT-PT was retained longer in SK-MEL-37 cells in comparison to their isotope control RIC. In clonogenic assays, 111In-DTPA-anti-NY-ESO-1-TAT-PT significantly reduced surviving fraction of SK-MEL-37 cells. Cytotoxicity was inversely proportional to specific activity and the concentration of cells exposed to 111In-DTPA-anti-NY-ESO-1-TAT-PT. siRNA knock down of NY-ESO-1 resulted in partial reversal of 111In-DTPA-anti-NY-ESO-1-TAT-PT associated cytotoxicity. These promising results obtained from the in vitro study has brought the probe further into in vivo study. In preliminary biodistribution studies in SK-MEL-37 xenograft-bearing mice, tumour:muscle ratio for 111In-DTPA-anti-NY-ESO-1-TAT-PT was statistically significant compared to the control RIC 48 h post injection. This clearly indicated that the probe can be delivered into tumour in in vivo model and the successful uptake of radioactivity increased the chance of causing cytotoxicity to tumour cells through DNA damage. All of these findings have suggested that intracellular cancer associated antigen NY-ESO-1 can be reached by protein transfection reagent and cell penetrating peptide and initiates DNA damage through radio-isotope mediated cytotoxicity. Therefore, it represents a novel approach to the treatment of CTA-expressing cancers.